Economic analyses of rubber and tea plantations and rubber-tea intercropping in Hainan, China - Guo Zhimei; Deegen Peter; Uibrig Holm; Zhang Yaoqi (Agroforestry Systems, 2006)
This study uses land expectation value (LEV) as a criterion to conduct economic analyses of natural rubber (Hevea brasiliensis) and tea (Camellia sinensis var. assamica) monoculture, and rubber-tea intercropping. We calculated LEV by using the Faustmann model that combines annual revenue flow from latex production with final timber harvest of rubber trees. Production and cost data were collected from Xinwei Farm in Hainan, China. We found that rubber-tea intercropping generated higher LEV than rubber and tea monoculture under current socio-economic circumstances. Sensitivity analysis has been conducted to examine the impacts on land expectation value by interest rate, prices of natural rubber and tea, and labor costs.
Keywords: Economic efficiency; Faustmann model; Land expectation value; Optimal rotation; Tropical land use